The Bukhorians We Don't Know or Sabbaq Bukhari - Literary Scholar - N.J. Bekova; D.F. Achilova (Genius Publishing Group, 2023)
From this article, information about the life and creative heritage of Abdul Qadir Karomatullah ibn Nematullah Sheikh Sabbaq Bukhari, who lived in the 20th century, was very poorly organized.
Keywords: Sabbag Bukhari; Saudi Arabia; tazkirah